Intercity onomastic terminology in Russian and French languages: a comparative aspect - Darafeyenka, Maryna L. (Journal of the Belarusian State University. Philology, 2022)
The results of the comparative analysis of intracity onomastic terms in Russian and French are presented. General and particular features of terms compound based on the material of Russian and French languages are established. The quantitative prevalence of differences over similarities is determined. It has been demonstrated that it is possible to find the same terms in two terminological systems, however, their meanings do not always coincide. Differences in terms usage and their scope are established by different theoretical approaches to the study of the onomastic conceptual system in general and inconsistent traditions of the compared onomastic schools in particular. It has been noted that in Russian and French terminology not all of categories of intercity names are designated by a special onomastic terms both, which has derived from the peripheral position of these units in the onymic space of the settlement. It has been established that at present we have more or less ordered system of Russian onomastic terms which allow us to describe the onym system of any city to the fullest. It is being emphasised that the existing List of basic onomastic terms, designed to organise international terminology, does not always contribute to the search for foreign equivalents of terms. It has been revealed that the main difficulties we encounter while comparing individual onomastic terminologies are related to the lacunarity, terminological redundancy for some fragments of the intercity onomasticon and unequal understanding (scope) of the same term in different onomastic schools of one or different countries.